CORONA DISCHARGE MICROMACHINING FOR THE SYNTHESIS OF NANOPARTICLES characterization and... applications. - Sahu, Ranjeet Kumar; Hiremath, Somashekhar S. ([S.l.] : CRC PRESS, 2019)
This book summarizes the fundamental and established methods for the synthesis of nanoparticles, providing readers with an organized and comprehensive insight into the field of nanoparticle technology. In addition to exploring the characterization and applications of nanoparticles, it also focuses on the recently explored corona discharge micromachining - Electrical Discharge Micromachining (EDMM) - method to synthesize inorganic nanoparticles. In the synthesis of nanoparticles, organic materials often play an indispensable role, such as providing stabilizers in the form of capping agents. This book will be of interest to advanced undergraduate and graduate students studying physics and engineering, as well as professionals and academics looking for an introduction to the nature and foundations of nanoparticle synthesis. Features: Provides diagnostic tools for the characterization of nanoparticles Explores the cutting-edge EDMM method for the synthesis and characterization of nanoparticles Discusses possible methods to overcome agglomeration of nanoparticles and achieve stable dispersion, in addition to examining the application suitability of synthesized nanoparticles
4.3 Electrical Discharge Machining (EDM)4.3.1 Salient Features of EDM; 4.3.2 EDM Cell; 4.3.3 Mechanism of EDM; 4.4 Electrical Discharge Micromachining (EDMM); 4.4.1 EDMM Approach for Nanoparticles Synthesis; 4.5 Prototype EDMM System; 4.5.1 Ultrasonicator; 4.5.2 Piezoactuator; 4.5.3 Pulse Generation and Control Module; 4.5.4 Tool Feed Control Module; 4.6 Summary; References; 5: Synthesis, Characterization, and Application Suitability; 5.1 Introduction; 5.2 Synthesis of Copper Nanoparticles; 5.2.1 Experimental Parameters; 5.2.2 Experimental Procedure
OCLC-licensed vendor bibliographic record.
Keywords: Nanoparticles; Nanostructured materials; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; SCIENCE / Nanostructures; SCIENCE / Physics; SCIENCE / Applied Sciences